Introduction: The ANDRILL McMurdo Ice Shelf (MIS) and Southern McMurdo Sound (SMS) drilling projects - Frank Niessen; Massimo Pompilio; Timothy Paulsen; Kurt S. Panter; Richard D. Jarrard (Geosphere, 2012)
Some of the greatest uncertainties in our understanding of Cenozoic global tectonics and climate can be traced back to our relatively meager knowledge about Antarctica9s continental lithosphere and its overlying continental glaciers. A trove of information about past tectonism and the behavior of the continental ice sheets lies buried along the submarine continental margins of Antarctica. In order to explore this area, there have been several international efforts over the last several decades to drill Cenozoic stratigraphic sequences within basins in the West Antarctic Rift system in the southern Ross Sea. The most recent of the Ross Sea drilling projects was part of the ANDRILL initiative (www.andrill.org) in which scientists from Germany, Italy, New Zealand, and the United States collaborated to acquire two high-resolution slim hole sedimentary cores from the southern Ross Sea. The papers within this Geosphere themed issue examine results associated with these projects. They are ultimately a result of significant efforts by a new generation of scientists who were willing and able to take the reins of leadership at the close of ANDRILL9s ancestor, the Cape Roberts Project. These papers speak to the importance of multidisciplinary science and international cooperation, and hopefully come at the dawn of further drilling and investigations of the scientific frontier represented by Antarctica9s continental margins.